Perpustakaan Cinet: Wadah Literasi Anak Usia Dini di Era Digital - Ramdhani, Khairul; Juniatmoko, Ronnawan (Transformatif : Jurnal Pengabdian Masyarakat, 2022)
Today's reading culture is very rarely found because of the times that continue to this day, let alone entering the era of globalization in which there are various kinds of digitization which in general all work can be done easily and quickly. The program, which was created in Cinet Hamlet, Bulurejo Village, Gondangrejo District, Karanganyar Regency, Central Java Province, is related to restoring reading interest during this very massive digitalization era, namely the Cinet Library. The method that devotees use is environmental observation. From the results of these observations, the devotees have not found one from all sides and corners of the literacy place in Cinet Hamlet, namely the library. The purpose of this service is to make children return to reading books even though the digitalization era has entered their age, which are still in elementary school.